A Phase III open-label, randomized, active controlled clinical study to assess safety, immunogenicity and lot-to-lot consistency of a bovine-human reassortant pentavalent rotavirus vaccine in Indian infants. Issue 52 (18th December 2018) - Rathi, Niraj; Desai, Sajjad; Kawade, Anand; Venkatramanan, Padmasani; Kundu, Ritabrata; Lalwani, Sanjay K.; Dubey, A.P.; Venkateswara Rao, J.; Narayanappa, D.; Ghildiyal, Radha; Gogtay, Nithya; Venugopal, P.; et al.
Highlights: Pentavalent reassortant rotavirus vaccine (BRV-PV) was tested for lot-to-lot consistency in Indian infants. The vaccine demonstrated safety profile similar to licensed Rotarix®. Lot-to-lot consistency in the immunogenicity of BRV-PV was demonstrated in terms of GMC ratios of IgA antibodies. The immune responses between the pooled BRV-PV arms and Rotarix® were comparable. Abstract: Background: A heat-stable bovine-human rotavirus reassortant pentavalent vaccine (BRV-PV, ROTASIIL®) was developed in India. In this study, the vaccine was tested for safety, immunogenicity and clinical lot-to-lot consistency. Methods: This was a Phase III, open label, randomized, equivalence design study. The primary objective was to demonstrate lot-to-lot consistency of BRV-PV. Subjects were randomized into four arms, three arms received Lots A, B, and C of BRV-PV and the control arm, received Rotarix®. Three doses of BRV-PV or two doses of Rotarix® and one dose of placebo were given at 6, 10, and 14 weeks of age. Blood samples were collected four weeks after the third dose to assess rotavirus IgA antibody levels. The three lots of BRV-PV were equivalent if the 95% Confidence Intervals (CIs) of the geometric mean concentration (GMC) ratios were between 0.5 and 2. Solicited reactions were collected by using diary cards. Results: The study was conducted in 1500 randomized infants, of which 1341 infants completed the study. The IgA GMC ratios among the three lots were around 1 (Lot A versus Lot B: 1.07; Lot A versus Lot C: 1.06; and Lot B versus Lot C: 0.99). The 95% CIs for the GMC ratios were between 0.78 and 1.36. The IgA GMCs were: BRV-PV group 19.16 (95% CI 17.37–21.14) and Rotarix® group 10.92 (95% CI 9.36–12.74) (GMC ratio 1.75; 90% CI 1.51–2.04). Seropositivity rates were 46.98% (95% CI 43.86–50.11) and 31.12% (95% CI 26.17–36.41). The incidence of solicited reactions was comparable across the four arms. No serious adverse events were associated with the study vaccines, except two gastroenteritis events in the BRV-PV groups. Conclusion: Lot-to-lot consistency of BRV-PV was demonstrated in terms of GMC ratios of IgA antibodies. The vaccine safety and immunogenicity profiles were similar to those of Rotarix®. Clinical Trials.Gov [NCT02584816] and Clinical Trial Registry of India [CTRI/2015/07/006034].